Optomechanics with two-phonon driving - Levitan, B A; Metelmann, A; Clerk, A A (arXiv.org, 2016)
We consider the physics of an optomechanical cavity subject to coherent two-phonon driving, i.e. degenerate parametric amplification of the mechanical mode. We show that in such a system, the cavity mode can effectively "inherit" parametric driving from the mechanics, yielding phase-sensitive amplification and squeezing of optical signals reflected from the cavity. We also demonstrate how such a system can be used to perform single-quadrature detection of a near-resonant narrow-band force applied to the mechanics with extremely low added noise from the optics. The system also exhibits strong differences from a conventional degenerate parametric amplifier: in particular, the cavity spectral function can become negative, indicating a negative effective photon temperature.